Vprašanje pravnega dometa analogne uporabe pravila prvega odstavka 397. člena ZGD-1 pri družbah z omejeno odgovornostjo - Dežman, Aljoša (Podjetje in delo, 2020)
The author examines whether in order to obtain the right to challenge the general meeting resolution, the properly invited shareholder must attend the general meeting of the limited liability company in person or through their proxy and announce the intended contestation, or whether the latter can be replaced by only a statement of the shareholder without physical participation (by them or their proxy) at the general meeting and without explicitly giving a statement of contestation at the general meeting due to the sensible application of the rules on the company.
Keywords: contestation; družba z omejeno odgovornostjo; economic status law; gospodarsko statusno pravo; izpodbijanje; limited liability company; shareholders assembly decision; sklep skupščine